Evolution of the Development of Core Competencies in Pharmaceutical Medicine and Their Potential Use in Education and Training - Stonier, Peter D.; Silva, Honorio; Boyd, Alan; Criscuolo, Domenico; Gabbay, Felicity J.; Imamura, Kyoko; Kesselring, Gustavo; Kerpel-Fronius, Sandor; Klech, Heinrich; Klingmann, Ingrid (Frontiers in Pharmacology, 2020)
The evolution of postgraduate vocational education and training in pharmaceutical medicine is described alongside the growth of this scientific-medical discipline and profession for the development of new medicines. Over the past 50 years, whilst the training of competent professionals for their work has been paramount, this has paralleled the need to engage with the rapid and complex changes in R&D technologies, patient and healthcare system needs, and the ethical and regulatory obligations applied to the development of medicines throughout their lifecycle. The move from unstructured training to formal programmes with syllabus, curricula and assessments for certification has been accompanied by educational changes to outcomes-based, learner-centred, competency-based programmes. The evolution of education and training along with the development of the set of core competencies for professional practitioners in pharmaceutical medicine are described. The application of core competencies in a harmonised, international framework of education and training in medicines development at the undergraduate, postgraduate and continuing professional development levels would invigorate the potential for having a competent workforce with the intent to provide faster access to better and appropriate medicines for patients worldwide.